2022
DOI: 10.4103/ijo.ijo_655_22
|View full text |Cite
|
Sign up to set email alerts
|

Complications in deep anterior lamellar keratoplasty – A retrospective interventional analysis in a large series

Abstract: Purpose: To analyze the complications in patients managed with deep anterior lamellar keratoplasty (DALK) for diseases of the anterior corneal stroma. Methods: This is a retrospective analysis of all the patients who underwent DALK in a tertiary care center in South India from 2010 to 2020. A total of 474 eyes in 373 patients were included in the study. Patients who underwent DALK for advanced keratoconus, keratoconus with Bowman’s membrane scar, healed hydrops, macular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The study reported a mean preoperative K2 value of 56.1 D and a mean postoperative K2 value of 45.5 D for the DALK group, a mean preoperative K2 value of 56.5 D, and a mean postoperative K2 value of 44.5 D for the PK group [12]. The advantages of DALK are well documented in the literature [13][14][15]. A study by Hakeem in 30 eyes comparing manual versus big bubble DALK found better postoperative BCVA in the big bubble variety [16].…”
Section: Discussionmentioning
confidence: 75%
“…The study reported a mean preoperative K2 value of 56.1 D and a mean postoperative K2 value of 45.5 D for the DALK group, a mean preoperative K2 value of 56.5 D, and a mean postoperative K2 value of 44.5 D for the PK group [12]. The advantages of DALK are well documented in the literature [13][14][15]. A study by Hakeem in 30 eyes comparing manual versus big bubble DALK found better postoperative BCVA in the big bubble variety [16].…”
Section: Discussionmentioning
confidence: 75%
“…suprachoroidal hemorrhage (SCH), which appears in 0.1% of the eyes undergoing a PKP 19 , 20 . To the best of our knowledge, none of the major papers on outcomes of DALK reported any SCH 21 24 . This fact alone might lead us to consider that DALK affects the uveal track and mainly the choroid less than PKP.…”
Section: Discussionmentioning
confidence: 99%